Identificação de regiões genômicas associadas a resistência à pseudocercos poragriseola na linhagem MAIII-16.159 de feijoeiro - Pádua, Paula Furtado de (2022)
The common bean (Phaseolus vulgaris L.) is widely grown in tropical and subtropical countries, and is an important source of proteins, carbohydrates, fiber, vitamins, and minerals. Angular leaf spot (ALS), caused by the fungus Pseudocercospora griseola, is of the most main diseases that affects the crop, leading to yield losses. The best strategy of disease control includes using resistant cultivars. The line MAIII-16.159 obtained from the recurrent selection program for ALS conducted by the Universidade Federal de Lavras in partnership with Embrapa, in Brazil has presented high resistance to P.griseola isolates. During the Common Bean Disease Workshop on Angular Leaf Spot and Root Rot, held in Skukuza, South Africa, in 2015, this line was indicated to compose the new international set of differential cultivars for the ALS. Despite the high level of resistance presented by this line, there is no information about its resistance genes. Therefore, it is important not only to identify these genes, but also to mapping the same. The MAIII-16.159 (resistant) line was crossed with the cultivar BRS Horizonte (susceptible) and advanced to the F7 generation by the SSD method (Single Seed Descent). 184 recombinant lines (RIL’s) were obtained. Phenotyping was carried out for ALS resistance in stage V2 and V3 using a isolate of race 63-63 of P. griseola and then genotyping using the DArTseq analysis facility (DArT Pty Ltd., Bruce, Australia). There was directional selection and loss of RILs, during advance of inbreeding generations, that is not be possible to carry out mapping. Therefore an association study was performed in this population that has presented high linkage disequilibrium. Two statistically significant associations for angular leaf spot resistance were identified at stage V2 and one at stage V3 (dart3496, dart7825, dart7260). These markers have presented a negative effect, that is, they act to reduce the severity of the ALS, two of which are located on chromosome Pv08 and one on Pv04. The locus found on chromosome Pv08 in V2 validated an earlier study region of the already described Phg-2 locus. This marker (dart7825) explained about 57% of the phenotypic variation caused by race 63-63. Markers dart3496 (Pv04) and dart7260 (Pv08) explained 53% and 44% of the phenotypic variation in V2 and V3, respectively. Therefore, the MAIII-16.159 line has alleles of greater effect located on chromosomes Pv08 and Pv04, responsible for resistance to P. griseola in both V2 and V3 developmental stages of the common bean.